Recovery of a bacteriocin-like inhibitory substance from Pediococcus acidilactici Kp10 using surfactant precipitation - Faizal Wong, Fadzlie Wong; Ariff, Arbakariya; Abbasiliasi, Sahar; Stuckey, David C. (Elsevier, 2017)
Bacteriocin is an important peptide which can be used as an anti-microbial agent in food. However, simpler and more cost-effective purification methods need to be developed compared to chromatography to enhance its commercial viability. Surfactant precipitation was employed for the first time to purify bacteriocin-like inhibitory substance (BLIS) from a fermentation broth of Pediococcus acidilactici Kp10, and the amount precipitated was investigated as a function of anionic surfactant (AOT) concentration, and pH. Protein recovery from the precipitate was accomplished using solvent extraction, and solvent type, NaCl concentration, and ionic strength of the final solution were optimised. Optimal conditions were; 1.05 mM of AOT at pH 4 for precipitation, and acetone extraction (with 1 mM NaCl), which resulted in an 86.3% yield, and 53.8 purification factor. This study highlighted the fact that surfactant precipitation can be used as a primary recovery method for BLIS from a complex fermentation broth.